Effect of deposited carbon nanotubes on interlaminar properties of carbon fiber‐reinforced epoxy composites using a developed spraying processing. Issue 1 (6th December 2012) - Shan, F.L.; Gu, Y.Z.; Li, M.; Liu, Y.N.; Zhang, Z.G.
Abstract: Carbon fiber‐reinforced epoxy composites, with incorporated carboxylic multiwall carbon nanotubes (CNTs), were prepared using vacuum‐assisted resin infusion (VARI) molding, and the in‐plane and out‐of‐plane properties, including mode‐I ( G Ic ) and mode‐II ( G IIc ) interlaminar fracture toughness, interlaminar shear strength (ILSS), tensile, and flexural properties were measured. A novel spraying technique, which sprays a kind of epoxy resin E20 with high viscosity after spraying the CNTs, was adopted to deposit the CNTs on the surface of carbon fiber fabric. The E20 was used to anchor CNTs on the fabric surface, avoiding that the deposited CNTs were removed by the infusing resin during VARI process. The spraying processing, including spraying amount and spraying sequence, was optimized based on the distribution of CNTs on the fibers. After that, three composite specimen groups were fabricated using different carbon fiber fabrics, including as‐received, CNT‐deposited with E20, and CNT‐deposited without E20. The effects of CNTs on the processing quality and mechanical properties of carbon fiber‐reinforced polymer composites were studied. The experimental results show that all studied laminates have uniform thickness with designed values and no obvious defects form inside the laminates. Compared with the composite without CNTs, depositing CNTs with E20 increases by 24% in the average propagation G Ic, by 11% in the propagation G IIc and by 12% in the ILSS, while it preserves the in‐plane mechanical properties, However, depositing CNTs without E20 reduces interlaminar fracture toughness. These phenomena are attributed to the differences in the distribution of CNTs and the fiber/matrix interfacial bonding for different spraying processing. POLYM. COMPOS., 2013. © 2012 Society of Plastics Engineers